FIRST INTERNATIONAL CONFERENCE ON LANGUAGE STUDIES AND RACISM: Open Letter (Estudos Linguísticos e Literários, 2024)
The First International Conference on Language Studies and Racism, held between December 6th and 8th, 2022 in Ilhéus, Bahía (Brazil), politically discussed the most diverse themes that have been circulating in the broad area of language studies in Brazil and that directly and indirectly bear upon the gravest expressions of racism in the country. This letter, compiled not as a final result of that meeting, but as dissemination of a series of agendas drawn from it, is proposed as a draft that brings together efforts undertaken over its course.